Penerapan model belajar mind mapping untuk meningkatkan pemahaman konsep kegiatan ekonomi dengan memanfaatkan sumber daya alam kelas IV sekolah dasar - Maria Magdalena; Jenny Indrastoeti Siti Poerwanti; Siti Wahyuningsih (Universitas Sebelas Maret, 2020)
The purpose of the research is to increase students' understanding of economic activities by utilizing natural resources. Subject of the research were 20 student from grade 4 at Palur 04 elementary school. This research was conducted in 2 cycles, each of which consisted of planning, implementation and reflection. In this study, researchers also collected data, the first was observation, then researchers conducted interviews with students and teachers, then used tests and used several documents to support research. In the data validities test technique, researchers used triangulation then source triangulation techniques. then for data analysis techniques, researchers use comparative descriptive techniques and critical analysis techniques. This study revealed that students' understanding of concepts improved after using a mind mapping model. it can be seen through the average value obtained. Scores obtained by students before applying this mind mapping model get an average value of 67.25 with a percentage of 40%. then continued with the first cycle, where the average score of students increased by 73.45 (65%). because it has not yet reached the indicator, the second cycle increases again, which then increases to 80.20 (90%)